Jaringan Syaraf Tiruan Memprediksi Penyakit Gerd menggunakan Metode Backpropagation : Studi Kasus : RSU. Bidadari Kota Binjai - Diaz Kuncoro; Akim M.H. Pardede; Siswan Syahputra (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2024)
The rapid development of technology in the globalization era has significantly impacted various aspects of life, including the healthcare sector. RSU Bidadari Binjai, as a healthcare provider, faces challenges in diagnosing and preventing Gastroesophageal Reflux Disease (GERD), a condition with high prevalence and serious complications such as Barrett’s esophagus and esophageal cancer. Therefore, a predictive system capable of early detection is needed to ensure quicker and more effective medical intervention. This research develops a computer-based predictive system using the backpropagation method in artificial neural networks to assist in diagnosing GERD by processing patient symptom data. The system's test results show an accuracy rate of 100% in predicting GERD complications based on the given symptoms, thus supporting more timely and accurate medical interventions.